Part I: epidemiology and risk factors for stress fractures in female athletes - Abbott, A.; Bird, M. L.; Wild, E.; Brown, S. M.; Stewart, G.; Mulcahey, M. K. (The Physician and Sportsmedicine, 2020)
Objectives: Stress fractures (SFx) are a common athletic injury, occurring in up to 40% of athletes at some point in their career. These injuries can cause pain, permanent disability, financial burden, and loss of playing time. This review presents updated epidemiology and comprehensive analysis of risk factors for stress fractures, especially as it pertains to female athletes.